South African new academics’ experiences of precarity: Becoming and unbecoming the condition of coloniality through collective reflexivity - Daniels, Nicole; Goolam Hoosen, Taahira; Jayakumar, Jaisubash; Behari-Leak, Kasturi (Critical Studies in Teaching and Learning, 2024)
The transition into Higher Education can be complex with South African new academics expected to drive institutional change and social transformation. We examine precarity from our situated geopolitical positioning, as a condition of coloniality and neoliberal forces. Our focus on racially marginalised new academics straddling multiple pedagogical roles addresses the challenges of needing to become collective reflexive agents, yet also unbecome conditions of coloniality. Through autoethnography, lived experiences of precarity as affective states are shown to co-produce displaced estrangement, undermine a coherent sense of self, and reinscribe colonial modes of doing and being. We argue that knowledge rooted in African-centred epistemologies offers new academics’ ways to collectively rally together to disrupt the status quo. This approach enriches the minimally understood concept of collective reflexivity. Our findings underscore the value of bringing decolonisation perspectives into conversation with reflexivity theories. We propose collective reflexivity can help new academics navigate their situational challenges.